2024
DOI: 10.3934/amc.2022023
|View full text |Cite
|
Sign up to set email alerts
|

$\mathbb{F}_{p^{m}}\mathbb{F}_{p^{m}}{[u^2]}$-additive skew cyclic codes of length $2p^s $

Abstract: <p style='text-indent:20px;'>In this paper, we first study the skew cyclic codes of length <inline-formula><tex-math id="M3">\begin{document}$ p^s $\end{document}</tex-math></inline-formula> over <inline-formula><tex-math id="M4">\begin{document}$ R_3 = \mathbb{F}_{p^m}+u\mathbb{F}_{p^m}+u^2\mathbb{F}_{p^m}, $\end{document}</tex-math></inline-formula> where <inline-formula><tex-math id="M5">\begin{document}$ p $\end{document}</tex-math><… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…In addition, recent studies have revealed that the resistance of Brucella spp. to various antibiotics, such as rifampicin, Yang et al 10.3389/fmicb.2024.1389859 Frontiers in Microbiology 16 frontiersin.org azithromycin, tetracycline, and so on, has been increasing (Wareth et al, 2021(Wareth et al, , 2022Celik et al, 2023;Rezaei Shahrabi et al, 2023;Beig et al, 2024). These studies indicate an increase in antibiotic resistance in intracellular Brucella, which urgently requires attention.…”
Section: Intracellular and Extracellular Brucella Strains Showed Diff...mentioning
confidence: 99%
“…In addition, recent studies have revealed that the resistance of Brucella spp. to various antibiotics, such as rifampicin, Yang et al 10.3389/fmicb.2024.1389859 Frontiers in Microbiology 16 frontiersin.org azithromycin, tetracycline, and so on, has been increasing (Wareth et al, 2021(Wareth et al, , 2022Celik et al, 2023;Rezaei Shahrabi et al, 2023;Beig et al, 2024). These studies indicate an increase in antibiotic resistance in intracellular Brucella, which urgently requires attention.…”
Section: Intracellular and Extracellular Brucella Strains Showed Diff...mentioning
confidence: 99%